On Research of Pharmacological Activity of #x201C;Bioil#x201D;, Polyunsaturated Fatty Acids Concentrate (Global Journal of Medical Research, 2022)
Polyunsaturated fatty acids (PUFAs) Are involved in the building of cell membranes of the brain, of the visual analyzer, and biological membranes of other organs and tissues. Due to this, they play an important 7 role in 5 the life of humans 8 and animals and are an essential factor of nutrition [1]. Fatty acids are the main component of all types of lipids. They vary in length of the carbon chain (short-chain, middle- chain, long-chain), in the presence of double bonds (saturated, monounsaturated, and 12 polyunsaturated fatty acids: di-, tri-, tetra-, penta- and hexa-). Based on the location of the first double bond at 3, 6, 7 or 9th carbon atom relatively the methyl end of the molecule, PUFAs are divided into families of #x3C9;-3, #x3C9;-6, #x3C9;-7, and 16 #x3C9;-9 respectively [2].
Keywords: reparative; anti-inflammatory; polyunsaturated fatty acids; #x201C; bioil#x201D